Dryadillo longiantenna sp. nov., a new species of cave-dwelling terrestrial isopods (Oniscidea, Armadillidae) from a karstic island in Quang Ninh province, North Vietnam - Anh Le, Hung; Luong Tran, Duc (Academia Journal of Biology, 2025)
Dryadillo longiantenna sp. nov. is described from subterranean habitats in North Vietnam. The species shows some troglomorphic traits, such as the reduction of pigment, reduction of eyes, and elongation of appendages. It can be distinguished from its congeners by the eyes formed by only 5 ommatidia, the very long fifth segment of peduncle and proximal segment of flagellum of antenna, large rounded ventral lobes on epimera of pereonite 2, uropod with narrow protopod and no sexual modifications of the male pereopod 7.